Characterization of Waste From Attiéké Factory: Case of Azito Village (Abidjan, Côte d’Ivoire) - Nazo Edith, Kpata-Konan; Felix, Konan Koffi; Francis, Kouame Yao.; Theophile, Gnagne; Kablan, Tano (European Scientific Journal, ESJ, 2016)
The control of the anaerobic digestion of cassava residues from attiéké factories requires their characterization to offer a better working environment to attiéké producers. This study concerns at first the quantity of solid residues of cassava, dough of crushed cassava and other waste generated by the process of attiéké production. The second aspect concerns the determination of some physicochemical parameters (COD, TKN, pH, COD/TKN). These two aspects were realized thanks to the use of a bag in synthetic fibers, a dynamometric steelyard with dial of diameter 17 cms, and the use of a gradual can of capacity 20 L. The results of this study showed that an average quantity of 1.53 tonne of manioc handled (treated) generates 1.14 m3 of effluents and 0.16 tonne of solid waste per day. These effluents are acid with a pH ranged between 2.54 and 4.80. So they have on average a DCO of 58.79 g/L for 0,71 g/L of nitrogen. All these parameters help control the optimal conditions of anaerobic digestion of cassava effluents in the manufacturing process of attiéké.